Do differences in plasticity during early growth lead to differing success in competition? A test using four co‐occurring annual Papaver. Issue 1 (26th September 2012) - Milberg, Per; Karlsson, Jan; Wessman, Lotta; Karlsson, Laila M.
Abstract Plant species differ in their ability to transform available resources to biomass and to respond in a plastic way to environmental circumstances; we hypothesized that such differences among four weed taxa of Papaver would explain differences in their competitive response. We first compared two populations each of Papaver rhoeas L., P. dubium L. ssp. dubium, P. dubium L. ssp. lecoqii (Lamotte) Syme and P. argemone L., grown in a greenhouse for 6 weeks in a nutrient gradient combined with two light treatments to elucidate possible differences in responses. As there were clear differences, a second experiment evaluated whether these differences also meant differences in competitive response, during early growth, when tested against two crops (wheat, rape). The assumption that competitive response was linked to the ability to transform nutrient and light to biomass was not supported: even though differences in extent of plasticity existed, the effect of competition was similar for the taxa. Thus, higher plasticity and ability to transform available recourses to biomass did not lead to stronger competitiveness for Papaver during early growth.